An audit of emergency hernia operations: Surrogate of system failure or incidentalomas? - Nkgudi, Boitumelo (Division of General Surgery, 2020)
Background: Hernia emergencies common surgery. Around 20 million groin hernia operations occur world-wide, and these form 70% of all hernia operations. Incisional hernias complicate 15- 30% of laparotomies and 20% of these present as emergencies. Watchful waiting is often applied for groin, ventral and incisional hernias in patients who are asymptomatic or those who are poor surgical candidates. The factors associated with poor outcomes include - elderly patients, multiple comorbidities, delays in presentation, those which are incarcerated or strangulated and delays in getting to theatre. Management of emergency hernias include resuscitative efforts to address life threatening problems, and thereafter performing the safest and most durable repairs. Aim: We aim to elucidate patient and health care systems factors that contribute to hernia emergency presentations and to document the mortality and morbidity of such presentations in our unit. Method: We aim to review case files of all patients above 18 years of age who had their emergency surgery for a complicated hernia. All elective cases will be excluded. Conclusion: This study will contribute to understanding emergency hernias in south Africa and will seek to improve patient care in our setting. A hernia registry has recently been established and thus we will be able to contribute to its foundation.